Segobriga, el enclave romano de los confines de la Celtiberia - Abascal Palazón, Juan Manuel, 1958-; Álvarez Martínez, José María, 1947-; Nogales Basarrate, Trinidad, 1960-; Rodá, Isabel (Badajoz: Museo Nacional de Arte Romano, 2014)
According Pliny the Younger, the Roman city of Segóbriga (Hispania citerior) are located at the southern end of Celtiberia (caput Celtiberiae) and was famous for the wealth of its mines of lapis specularis. In the time of Augustus, probably circ. 15 BC, the spot reached the category of municipium iuris Latini and was already highly urbanized, with the construction of a new wall, forum, curia, porticus, etc. In time of the Flavian emperors were built the theatre and the amphitheatre, located outside the city walls, and in the second half of the second century was built the circus.
Keywords: Roma -- Historia -- 30 a.C.-476 d.C. (Imperio); Península Ibérica